Need of Marketing of India as a Tourist Destination: Evaluation of India's Performance in Tourism - Mishra, Amitabh; Ojha, Nisha Kant (Prabandhan: Indian Journal of Management, 2015)
India is a country with a huge variety of tourism products. Each corner of India is unique and different from the other when it comes to food, music, dances, festivals, weather, ecology, flora and fauna, and so forth. India offers a totally distinct tourism experience with its diverse geography and cultures. The present research paper mainly evaluated the need of marketing of India as a tourism destination. The research paper briefly lists the major promotional schemes of the Government of India and examines the performance of the Indian tourism industry in comparison with other major countries of the world (in general) and Asia-pacific (in particular). The study finally concludes that the marketing and promotional efforts have resulted in improved performance of the tourism industry in India. However, India is still unable to utilize its full tourism potential and needs to put in more rigorous efforts for tourism promotion as well as marketing.